The role and place of azelaic acid in the routes of patients with acne vulgaris - E. S. Snarskaya (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
The review presents data from foreign and domestic clinical studies on the efficacy and safety of azelaic acid (Skinoren) in the treatment of acne vulgaris. New aspects of pathogenesis are presented, an analysis of the database of systematic reviews of Russian, European, American researchers is presented, including an analysis of the database of systematic reviews of the Cochrane Systematic Review Intervention Version of the Cochrane Skin Group (2020) comparative studies on the effectiveness of azelaic acid, Skinoren and other topical topical medications for the treatment of acne vulgaris. Possibilities of monotherapy with the preparation of azaelaic acid Skinoren and variants of combined treatment, in particular, a combination of azelaic acid with topical retinoids, benzoyl peroxide, systemic and topical antibiotics for the treatment of acne of varying severity, are shown. Reliable efficacy, safety, the possibility of long-term therapy, high compliance allow us to conclude that Skinoren is highly effective in treating acne, and a number of priority complex advantages, such as the presence of anti-inflammatory, antibacterial, anti-keratinizing, antiandrogenic and anti-tyrosinase action, allow Skinoren to be considered as optimal. topical agent for long-term and safe treatment of acne and prevention of the development of post-acne symptom complex.